FRI0413 Clinical Risk Factors for The Presence and Development of Vertebral Fractures in Patients with Ankylosing Spondylitis. (15th July 2016) - Maas, F.; Spoorenberg, A.; van der Slik, B.P.; van der Veer, E.; Brouwer, E.; Bootsma, H.; Bos, R.; Wink, F.R.; Arends, S.
Abstract : Background: Vertebral fractures are the hallmark of bone fragility and are frequently present in patients with ankylosing spondylitis (AS). For treating rheumatologists, it is important to know which patients already have vertebral fractures and which patients are at risk to develop new fractures. Limited longitudinal data are available concerning the development of new vertebral fractures in AS. Objectives: To investigate the prevalence and incidence of radiographic vertebral fractures and the association with patient characteristics, clinical assessments, and medication use in a large prospective cohort of patients with ankylosing spondylitis (AS) in daily clinical practice. Methods: Consecutive AS patients from the Groningen Leeuwarden AS (GLAS) cohort with baseline and 2-year lateral radiographs of the thoracic and lumbar spine were included. Radiographs were scored for vertebral fractures by two readers according to the method of Genant et al . Vertebral fractures were defined as ≥20% reduction in vertebral height. Severity of fractures were divided into mild (20–25% reduction), moderate (25–40% reduction), and severe (>40% reduction) fractures. Differences in baseline characteristics were explored between patients with and without radiographic vertebral fractures. Results: Of 292 included AS patients, 70% were male, 82% HLA-B27+, mean age was 43±13 years, median symptom duration 16 (IQR: 8–25) years, and mean BASDAI 5.3±2.2. Radiographic vertebral fractures were present in 59 (20%) patients at baseline. During 2 years of follow-up, 15 (6%) patients developed new vertebral fractures and 7 (2%) showed an increase in severity of existing fractures. Most fractures were mild and located in the mid-thoracic and thoracolumbar region of the spine. The presence of vertebral fractures was significantly associated with older age, higher BMI, longer smoking duration, larger occiput-to-wall distance, more spinal radiographic damage, and lower hip BMD. Occiput-to-wall distance was identified as an independent risk factor for prevalent vertebral fractures; 44% of the patients with hyperkyphosis (occiput-to-wall distance ≥10 cm) had vertebral fractures. The development of new or progressive vertebral fractures was also associated with older age and low BMD. Patients using NSAIDs at baseline showed less prevalent (18% vs. 31%) and incident (5% vs. 17%) vertebral fractures than patients without NSAIDs. Conclusions: In this large AS cohort in daily clinical practice, radiographic vertebral fractures were frequently present, especially in older patients with more advanced disease, low hip BMD, and a less healthy lifestyle. Interestingly, NSAID use was associated with a reduced vertebral fracture risk. Acknowledgement: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: F. Maas: None declared, A. Spoorenberg Grant/research support from: Abbvie, Pfizer, UCB, Consultant for: Abbvie, Pfizer, MSD, UCB, Novartis, B. van der Slik: None declared, E. van der Veer: None declared, E. Brouwer Grant/research support from: Pfizer, H. Bootsma: None declared, R. Bos Grant/research support from: Pfizer, F. Wink Consultant for: Abbvie, S. Arends Grant/research support from: Pfizer